Central muscarinic blockade interferes with retrieval and reacquisition of active allothetic place avoidance despite spatial pretraining - Vales, Karel; Stuchlik, Ales (Behavioural brain research, 2005)
Animal navigation to hidden goals (place navigation) ranks among the most intensively studied types of behaviour because it requires brain representations of environments in the form of cognitive maps, demonstrated to depend on hippocampal function. Intact function of muscarinic receptors in the brain was originally assumed to be crucial for place navigation, however, recent studies using non-spatial pretraining demonstrated that animals with central blockade of muscarinic acetylcholine receptors can also learn and retrieve spatial memory engrams. In the present study we addressed whether navigation in the active allothetic place avoidance (AAPA) task, which requires animals to separate spatial stimuli into coherent representations and navigate according to the representation relevant for the task, is dependent on intact muscarinic receptors in the brain. We studied the effect of three doses of scopolamine (0.5, 1.0 and 2.0mg/kg) administered 20 min prior to training on the retention of the AAPA and re-acquisition of the AAPA in a new environment. The dose of 2.0mg/kg was found to impair both AAPA retention and re-acquisition of the AAPA in a new environment, whereas the 1.0mg/kg dose only impaired the reinforced retention of AAPA. It is concluded that, unlike navigation in classic paradigms, efficient orientation in the AAPA task is critically dependent on muscarinic receptors in the brain.
Keywords: rozvrh dávkování léků; Analysis of Variance; Animals; vztah mezi dávkou a účinkem léčiva; Muscarinic Antagonists; Retention, Psychology; rozpomínání; Rats, Long-Evans; Avoidance Learning; Space Perception; pohybová aktivita; časové faktory; Time Factors; chování zvířat; retence (psychologie); Mental Recall; Drug Administration Schedule; antagonisté muskarinových receptorů; Spatial Behavior; Dose-Response Relationship, Drug; analýza rozptylu; potkani Long-Evans; Male; skopolamin; učení vyhýbat se; krysa rodu Rattus; Behavior, Animal; Motor Activity; vnímání prostoru; Scopolamine; Maze Learning; zvířata; mužské pohlaví; bludiště - učení; Rats; prostorové chování